ARCHEAN MAGMATISM IN THE NORTHWESTERN MARGIN OF THE ANCIENT VODLOZERO DOMAIN NEAR LAKE OSTER, KARELIA: GEOLOGY, GEOCHEMISTRY, AND PETROLOGY - Chekulaev V.P.; Lobach-Zhuchenko S.B.; Arestova N.A.; Guseva N.S.; Kovalenko A.V.; Krylov I.N. (My University, 2002)
Detailed geological, geochemical, and petrological data were obtained on Archean magmatic rocks sampled in the area of Lake Oster, which is the northwestern margin of the ancient Vodlozero domain with tectonically combined crustal fragments representing rock complexes of diverse ages and generated under different conditions. The oldest rocks (2900-3020 Ma) affiliate with two rock associations: (1) komatiite, serpentinite, basalt, and gabbro-amphibolite occurring as individual lenses and blocks in the central part of the area (they are oceanic crustal fragments of composition resembling modern ophiolites) and (2) andesite, basalt, quartz diorite, and trondhjemite porphyry (which were supposedly derived from sources of different compositions, under varying P-T conditions, and high water contents, as in the environments of ensimatic island arcs). The next magmatic pulse (at 2800-2900 Ma) gave rise for metavolcanics of andesite-dacitic composition and granites of the I type of the Oster intrusion and hypabyssal granitoid complexes. Most melts that crystallized during this time were derived at significant depths (P = 15 kbar and more) with the participation of basalts and high-Mg andesites. Judging from the Nd isotopic data, the sources of these rocks included ancient rocks with ages of 3 Ga and older, which implies the presence of an ancient sialic crust. A combination of the aforementioned features of the rock complexes produced during this stage does not provide unambiguous indications of the geodynamic environment. On the one hand, the magmatism can be interpreted as marking the western margin of the ancient Vodlozero domain, but, on the other hand, the composition and genesis of the rocks are generally consistent with the plume model. Magmatism at 2.70 ± 0.05 Ga produced the granitoids of the Geyneoja pluton and mafic and ultramafic intrusions and dikes. The composition of the mafic rocks provides evidence of their crystallization from deep-seated, crustally uncontaminated melts. The granites were derived from a crustal source at shallow depths and a very high geothermal gradient (at least 50°C/km). The genesis of these rocks could be related to the ascent of a mantle plume. This is in good agreement with the development of a mantle plume beneath the whole Karelian granite-greenstone terrane at 2700 Ma.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей